2020
DOI: 10.1093/sf/soaa081
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Insider-Outsider Divide: Heterogeneous Effects of Organizational Identity and Category Taken-for-Grantedness on Conformity

Abstract: Categories that become taken-for-granted tend to acquire rule-like standing. That is, people begin to strongly expect certain behaviors from entities that have claimed affiliation with them, and these expectations tend to induce conformity. However, conformity does not always ensue, and we lack an explanation of why the effects of category taken-for-grantedness might diverge. In this paper, we propose that the effects of increasing category taken-for-grantedness hinge upon an organization’s identity. We first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
(52 reference statements)
1
7
0
Order By: Relevance
“…Organizational identification significantly predicted faculty conformity ( β = 0.255, p < 0.001, M3 in Table 2 ), consistent with Paolella and Syakhroza (2021) ; thus, H1 is supported. Regression analysis of moderated mediation shows that the interaction between organizational identification and conflict management style shows faculty conformity ( β = 0.105, p < 0.01, M5 in Table 2 ); thus, H2 and H3 is supported.…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…Organizational identification significantly predicted faculty conformity ( β = 0.255, p < 0.001, M3 in Table 2 ), consistent with Paolella and Syakhroza (2021) ; thus, H1 is supported. Regression analysis of moderated mediation shows that the interaction between organizational identification and conflict management style shows faculty conformity ( β = 0.105, p < 0.01, M5 in Table 2 ); thus, H2 and H3 is supported.…”
Section: Resultssupporting
confidence: 68%
“…The partial mediating effects showed that organizational identification has a positive impact on formalization of organizational structure ( Maraghoush et al, 2021 ). A higher level of organizational identification is more likely to produce faculty conformity ( Paolella and Syakhroza, 2021 ), and formalization of organizational structure can also contribute to faculty conformity ( Borry et al, 2018 ; Li et al, 2021 ). This validates the social contagion theory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Identification is an attitude, or an internal process that maintains relationships with the group or intervenes in an individual's attitudes (Wu et al, 2022). Thus, the higher the organizational identification, the more likely it will produce conformity (Paolella and Syakhroza, 2021). When faculty members identify with the organization they serve, they incorporate organizational values and cultural goals into their personal objectives, internalize various behavioral codes in the formalization of organizational structure, and produce behaviors of faculty conformity that are consistent with organizational goals (De Cremer and Tyler, 2005;Wu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%